2019
DOI: 10.3389/fneur.2019.00119
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA Methylation and Adenosine in Ketogenic Diet for Pharmacoresistant Epilepsy: Focus on Epileptogenesis and Associated Comorbidities

Abstract: Epilepsy is a neurological disorder characterized by a long term propensity to produce unprovoked seizures and by the associated comorbidities including neurological, cognitive, psychiatric, and impairment the quality of life. Despite the clinic availability of several novel antiepileptic drugs (AEDs) with different mechanisms of action, more than one-third of patients with epilepsy suffer with pharmacoresistant epilepsy. Until now, no AEDs have been proven to confer the efficacy in alteration of disease progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 110 publications
0
20
0
2
Order By: Relevance
“…In addition, improvement of mitochondria function leads to energy reserve, then activates ATP-sensitive potassium channels, which would stabilize synapse and attenuate neuronal excitability (36). Moreover, adenosine may be play a crucial role associated with this procession via an adenosine-dependent DNA methylation modulation (37). Furthermore, other researchers have showed that the KD has a protection against oxidative stress and mitochondrial dysfunction derived from epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, improvement of mitochondria function leads to energy reserve, then activates ATP-sensitive potassium channels, which would stabilize synapse and attenuate neuronal excitability (36). Moreover, adenosine may be play a crucial role associated with this procession via an adenosine-dependent DNA methylation modulation (37). Furthermore, other researchers have showed that the KD has a protection against oxidative stress and mitochondrial dysfunction derived from epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the few available clinical studies indicate that a KD has significant disease-modifying impacts, leaving some patients seizurefree even after discontinuation of the KD. 237,238 Notably, the KD has been most successful in mediating seizures in pediatric epilepsy. In a randomized controlled clinical trial, the impacts of a 3-month long trial of a KD was studied in children between the ages of 2 and 16 years, diagnosed with either generalized or focal epilepsy who had at least a seizure per day.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…239 Another pediatric study, which focused on children with pharmacoresistant epilepsy, showed after introducing a modified Atkins diet (a less restrictive variation of the KD), 30% of children experienced 90% seizure reduction and 52% of children experienced 50% seizure reduction after 3 months. 238,240 In an adult model, 32% of adult patients with pharmacoresistant epilepsy showed >50% seizure reduction using a KD. 237,238 While the therapeutic impact of adenosine augmentation is the focus of this section, it is important to note that the KD offers seizure control through other mechanisms as well.…”
Section: Dietary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is also a good way to prevent the development of epilepsy in clinic by identifying and avoiding the risk factors for epileptogenesis after certain precipitating events [ 23 , 24 ]. Additionally, a ketogenic diet, the high-fat, low-carbohydrate composition, as an alternative metabolic therapy for paediatric DRE, has also proved to be a promising disease-modifying for epilepsy or anti epileptogenic therapy [ 25 ]. However both of these are beyond the scope of this review.…”
Section: Significance Of Antiepileptogenic Therapymentioning
confidence: 99%